(untitled) (Zaranie Śląskie, 2021)
The article is an attempt to reconstruct and describe a series of dramatic events which took place in Upper Silesia in the times of the typhus outbreak, which raged across a few counties in the years 1847–1848. The starting point are the written ac- counts by a group of Upper Silesian doctors, who published a booklet reviewing the causes and course of the epidemic, as well as fragments from a diary by Max Ring, a doctor and writer residing in the Gliwice County. Both texts offer a medi- cal, social and ethical perspective on the spread of the disease and – importantly – help understand the socio-political relations prevalent in the region, as well as the relations between the Prussian government, the Berlin metropolis and the province-based officials. The report by a Berlin doctor, Rudolf Virchow, assigned by the Ministry of Health to investigate the situation (1848), is an interesting way to enhance the knowledge of the outbreak, of the regional health service and of the difficult, unsolved problems of hygiene, education and social in equalities in Upper Silesia. The article documents – on the one hand – the efforts of local doc- tors to bring relief to the sick and – on the other hand – their commitment to the reform of the health system, whose aim was to provide quality health service to the poorest group of Upper Silesians.